2019
DOI: 10.3390/ani9080475
|View full text |Cite
|
Sign up to set email alerts
|

Animal Images Database: Validation of 120 Images for Human-Animal Studies

Abstract: Simple SummaryWith the general goal of increasing knowledge about how individuals perceive and evaluate different animals, we provide normative data on an extensive set of open-source animal images, spanning a total of 12 biological categories (e.g., mammals, insects, reptiles, arachnids), on 11 evaluative dimensions (e.g., valence, cuteness, capacity to think, acceptability to kill for human consumption). We found that animal evaluations were affected by individual characteristics of the perceiver, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 80 publications
4
54
0
2
Order By: Relevance
“…We aimed to employ specifically the species eliciting one strong discrete emotion to avoid interference in the evaluation and interpretation of the results. The stimuli were selected according to previous studies as follows: first, we selected top-rated species from studies using visual picture stimuli, from Polák et al [ 34 ] (red panda, rat, louse, roundworm, tapeworm, moth, fly larva, and cockroach), Rádlová et al [ 23 ] (rattlesnake), Frynta et al [ 25 ] (frog and toad), Janovcová et al [ 26 ] (crocodile, turtle, lizard, coral snake, and blind snake), Peléšková [ 35 ] (ostrich, shoebill, eagle, condor, and guineafowl), Possidónio et al [ 33 ] (elephant, lion, bear, wolf, tiger, shark, piranha, scorpion, crab, beetle, butterfly, giant panda, bat, tick, earthworm, leech, and rabbit), and Landová et al [ 31 ] (rhinoceros, hippopotamus, buffalo, hyena, mole rat, and porcupine). However, the research covering all animal taxa has not yet been completed (mainly in the case of extremely variable invertebrates).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We aimed to employ specifically the species eliciting one strong discrete emotion to avoid interference in the evaluation and interpretation of the results. The stimuli were selected according to previous studies as follows: first, we selected top-rated species from studies using visual picture stimuli, from Polák et al [ 34 ] (red panda, rat, louse, roundworm, tapeworm, moth, fly larva, and cockroach), Rádlová et al [ 23 ] (rattlesnake), Frynta et al [ 25 ] (frog and toad), Janovcová et al [ 26 ] (crocodile, turtle, lizard, coral snake, and blind snake), Peléšková [ 35 ] (ostrich, shoebill, eagle, condor, and guineafowl), Possidónio et al [ 33 ] (elephant, lion, bear, wolf, tiger, shark, piranha, scorpion, crab, beetle, butterfly, giant panda, bat, tick, earthworm, leech, and rabbit), and Landová et al [ 31 ] (rhinoceros, hippopotamus, buffalo, hyena, mole rat, and porcupine). However, the research covering all animal taxa has not yet been completed (mainly in the case of extremely variable invertebrates).…”
Section: Methodsmentioning
confidence: 99%
“…Possidónio et al [ 33 ] used 120 pictures from 12 biological categories throughout the whole animal kingdom, but they examined dimensions other than basic emotions (e.g., valence, cuteness, dangerousness). Polák et al [ 34 ] investigated fear and disgust elicited by pictures of the 25 most common phobic animals.…”
Section: Introductionmentioning
confidence: 99%
“…As part of an unrelated study, perceived beauty of all images in the Animal Images Database (Possidónio et al, 2019) was assessed on a 11-point scale (0 = Not at all, 1 = Very much so; Nmean = 45.1). The beauty scale was comprised of the following items: beautiful, attractive, good-looking, appealing, ugly (reverse scored),…”
Section: Procedures and Materialsmentioning
confidence: 99%
“…Images used in Study 5a (taken from Possidónio et al, 2019). Beautiful animals are displayed in the top row and ugly animals are displayed in the bottom row.…”
Section: Figurementioning
confidence: 99%
“…For instance, beliefs about animals' minds influence attitudes toward animal use among both adults (Knight et al, 2004) and children (Hawkins & Williams, 2016). When seeing images of various animals, people's moral attitudes toward animals are related to their evaluations of animals' mental capacities such as the capacity to feel and think (Possidónio et al, 2019). Evidence has shown that intelligence information about a hypothesized alien animal increases people's moral standing judgment, especially when the animal is described as harmful (Piazza et al, 2014).…”
mentioning
confidence: 99%